Reliability based design of earth retaining structures - Loh, May Har. (2008)
The deterministic analysis of anchored sheet pile wall does not reflect the uncertainty in the loading, soil and water fluctuation parameters. Ambiguities could also arise from different definitions of safety factor. Three methods of introducing safety factors into deterministic design calculation are currently used in practice: Method A: Embedment depth is multiplied by factor (Fd); Method B: Gross passive resistance is factored (Fp); Method C: Shear strength parameters are divided by a factor (Fs).